Community Radio Research Trends in Communication Science: A Co-Authorship Bibliometric Analysis - Sjuchro, Dian Wardiana; Rahmatullah, Tansah; Nurfauziah, Isni (Jurnal Kajian Jurnalisme, 2025)
The lack of research on community radio is one of the obstacles to gaining an in-depth understanding of the relevant development and dynamics. Collaborative research is believed to be the alternative solution as a wider research range increases interest in the study. Further, increased interest can generate a greater contribution to community radio. Using Bibliometrics, this study analyzed the development trend of co-authorship-based community radio research from 1999 to March 2024. It found several significant findings. Firstly, there are indications that the topic of community radio is of less interest in scientific literature due to the limited number of publications, only 75 articles. Secondly, there is a drastic downward trend in the number of publications on community radio over some time, from 2017 to 2024. Thirdly, from the analysis of researcher networks (co-authorship), there is no overall centralized pattern of researcher relationships. While there are some partial relationships among researchers, there must be a consistent or centralized pattern in the community radio research network. Research on community radio requires methodological renewal by investigating new and innovative approaches and collaborations that allow for the expansion of research networks.